Arabidopsis thaliana trehalose-6-phosphate phosphatase gene TPPI enhances drought tolerance by regulating stomatal apertures. (3rd April 2020) - Lin, Qingfang; Wang, Song; Dao, Yihang; Wang, Jianyong; Wang, Kai
Abstract : AtTPPI enhances drought tolerance by triggering ABA-mediated stomatal closure, increasing primary root length, and finally reducing the transpiration rate. Abstract: Transpiration occurs through stomata. The alteration of stomatal apertures in response to drought stress is an important process associated with water use efficiency (WUE). Trehalose-6-phosphate phosphatase ( TPP ) family genes have been reported to participate in adjustment of stomatal aperture. However, there have been no reports of the trehalose metabolism pathway genes improving WUE, and the upstream signalling pathway modulating these genes is not clear. Here, we demonstrate that a member of the TPP gene family, AtTPPI, confers drought resistance and improves WUE by decreasing stomatal apertures and improving root architecture. The reduced expression of AtTPPI caused a drought-sensitive phenotype, while its overexpression significantly increased drought tolerance. Abscisic acid (ABA)-induced stomatal closure experiments confirmed that AtTPPI mutation increased the stomatal aperture compared with that of wild-type plants; in contrast, overexpression plants had smaller stomatal apertures than those of wild-type plants. Moreover, AtTPPI mutation also caused stunted primary root length and compromised auxin transport, while overexpression plants had longer primary root lengths. Yeast one-hybrid assays showed that ABA-responsive element-binding factor1 (ABF1), ABF2, and ABF4 directly regulated AtTPPI expression. In summary, the way in which AtTPPI responds to drought stress suggests that AtTPPI -mediated stomatal regulation is an important mechanism to cope with drought stress and improve WUE.